Uplifting the socio-economic empowerment of women through handicraft industry - Shahina Bano; Neelam Farid; Asia Ashfaq; Siti Mas'udah (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Empowerment is seen as being capable of making choices about job, marriage, mobility, entertainment, and the number of children. The present study focused on the role of handicraft businesswomen, their experiences, and the role of handicraft business as a tool of empowerment for women in Gilgit, Pakistan. The study was limited to the experiences of women producing handicrafts and viewed as socio-economic empowerment for those who are producing handicrafts. This study employed a qualitative research design. The thematic analysis of interviews of the craftswomen showed that they were empowering themselves economically and socially through handicraft business. The research findings reinforced the objectives of the study that the craftswomen perceive empowerment as economic independence and the income generated through handicrafts strengthens their economic as well as social position in society. This study concludes that their economic and social position becomes stronger after starting to earn income. These women also felt like the source of change in terms of motivation, inspiration, and encouragement for the other women in the society. They viewed and regarded the skill of handicrafts as the source of income and financial support for their families.